International and national regulation of intentional vessel-source pollution in Arctic ice-covered areas - Neves, Maria Madalena Das (Universitetet i Tromsø, 2010)
It is now generally accepted that the impacts of climate change in the Arctic Ocean will, over the next decades, determine its transformation from a permanently ice-covered and virtually untraversable area into a seasonally navigable sea subject to the increase of commercial navigation opportunities. This increase of both intra- and trans-Arctic shipping, specifically through Arctic ice-covered areas, poses great pressures and risks in terms of impacts to the Arctic marine environment, its living resources and its biodiversity. Thus, the objective of this thesis is to examine international and national regulation of intentional vessel-source pollution in Arctic ice-covered areas and assess if, considering the increase of vessel traffic and the impact of climate change in those areas, it is adequate to protect the marine environment, living resources and biodiversity of the Arctic.